Cultivar-dependent differences in plant bud microbiome and functional gene pathways in woody plants commonly used in urban green space - Roslund, Marja I; Galitskaya, Polina; Saarenpää, Mika; Sinkkonen, Aki (Oxford University Press, 2024)
Plant richness and microbiota have been associated with plant health; hardly any studies have investigated how plant taxa differs in microbiota in the context of human health. We investigated the microbial differences in buds of 83 woody plant taxa used in urban green spaces in hemiboreal climate, using 16S rRNA and whole metagenome shotgun sequencing. Bud microbial community was the richest in Cotoneaster Nanshan and C. integerrimus, and Malus domestica cultivars “Sandra” and “Lobo” and poorest in Ribes glandulosum. Metagenomic shotgun sequencing of two M. domestica and four Ribes varieties confirmed differences in taxa in bud microbiota and indicated higher siderophore synthesis in Malus. Microbial richness, including bacteria, archaea, and viruses, and functional richness of gene pathways was higher in Malus compared to Ribes. The 10 most abundant amplicon sequence units, often referred as species, belonged to the phylum Proteobacteria. The differences between plant taxa were evident in classes Alpha- and Gammaproteobacteria, known for potential human health benefits. Since environmental microbiota contributes to human microbiota and immunoregulation, horticultural cultivars hosting rich microbiota may have human health benefits. Further studies are needed to confirm the effectiveness of microbially-oriented plant selection in optimizing human microbiota and planetary health.
Keywords: plant bud microbiome; shotgun metagenomes; planetary health; urban green space